(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
The article discusses ways to resolve conflicts in project team management in investment projects the opinions of the world’s leading scientists were studied, In investment projects, conflicts have been identified in the management of the project team, Human resources manage theories Systematized , Management a comparative analysis of technology was carried out, reasonable conclusions and proposals were developed on ways to resolve conflicts in the management of the project team in investment projects.